U-Model and U-Control Methodology for Nonlinear Dynamic Systems. (30th June 2020) - Zhang, Weicun; Zhu, Quanmin; Mobayen, Saleh; Yan, Hao; Qiu, Ji; Narayan, Pritesh
Abstract : This study presents the fundamental concepts and technical details of a U -model-based control ( U -control for short) system design framework, including U -model realisation from classic model sets, control system design procedures, and simulated showcase examples. Consequently, the framework provides readers with clear understandings and practical skills for further research expansion and applications. In contrast to the classic model-based design and model-free design methodologies, this model-independent design takes two parallel formations: (1) it designs an invariant virtual controller with a specified closed-loop transfer function in a feedback control loop and (2) it determines the real controller output by resolving the inverse of the plant U -model. It should be noted that (1) this U -control provides a universal control system design platform for many existing linear/nonlinear and polynomial/state-space models and (2) it complements many existing design approaches. Simulation studies are used as examples to demonstrate the analytically developed formulations and guideline for potential applications.